Development of gluten-free cocos nucifera (coconut) pulp flour and its impact on quality of Malay traditional kuih / Aziz Caliskan - Caliskan, Aziz (2020)
Gluten is an essential protein which is found in cereal crops such as wheat, rye, barley, and oat. It exhibits an elasticity property that aids in the shaping of food products into various suitable shapes and forms. However, despite its crucial role in food production, it has a negative impact on gluten intolerant individuals. Hence, the motivation behind this study to produce an alternative gluten-free flour from leftover coconut pulp (LOCP). The physicochemical properties (colour, water activity, and milling yield), chemical (proximate analysis, gluten, and peroxide value), and microbial content of LOCP being identified.